HUBUNGAN FUNGSI KOGNITIF DENGAN KEPATUHAN PENGGUNAAN MEDIKASI PADA LANSIA DI KELURAHAN GIRIAN PERMAI KOTA BITUNG - Abigail Asfas Tandilangi; Regina Makawimbang (Fakultas Ilmu Keperawatan Universitas Advent Indonesia, 2019)
Elderly is a life process that is characterized by a decline in cognitive function that can cause the inability to carry out activities, especially for the elderly who are undergoing treatment. The purpose of this study was to determine whether there is a relationship between cognitive function and compliance with the use of medication in the elderly in Girian Permai Village. The methods used were observational analytic and cross-sectional. Data were collected using a Mini-Mental State Examination (MMSE) questionnaire for cognitive function and the Morisky Medication Adherence Scale (MMAS) for compliance with medication use. The results showed 26 (52%) elderly experienced moderate cognitive impairment, and 38 (76%) elderly had low adherence to the use of medication, while the results of the correlation test between cognitive function and compliance with the use of medication showed significant values ​​p = (0.008). Researchers' recommendations for the community is to pay more attention and provide support to the elderly who are around the neighborhood, especially specifically for the elderly who are undergoing treatment, so that they can use the drug obediently.